Rancang Bangun Monitoring Getaran Jembatan Rangka Baja Soekarno-Hatta Malang sebagai Penilaian Kondisi Bangunan Atas Jembatan Melalui Web - Choirul Huda (Jurnal Jaringan Telekomunikasi, 2017)
This study aims to assist the related agencies and UPT to determine the performance of the bridge building so that further handling can be carried out from the results of the identification that has been carried out. The results show that monitoring bridge vibration via the web can be displayed properly the values ??and acceleration data graphs of the X, Y and Z axes as well as the FFT. Obtained the actual natural frequency value of the Soekarno Hatta Malang bridge is 0.28 Hz and an average acceleration is 0.12 mm / sec. QOS results with an average delay parameter of 35 ms, 0% packet loss, and a throughput of 0.024 Mbit / s when opening the main page of the webserver. accelerometer sensor MMA7455 requires 5V feed and ground and the sensor output is on a pin connected to the microcontroller analog input. Vibration measurements are carried out in the middle of the bridge span because for the purposes of measuring the minimum mode, by measuring in the minimum mode it can be seen the state of the service boundary of a bridge in real time through the website.